ANALISIS DISPARITAS DALAM PENJATUHAN PUTUSAN BAGI PELAKU TINDAK PIDANA “MAIN HAKIM SENDIRI” (EIGENRICHTING). - Nuriana, Adhinda Ratih; Rustamaji, Muhammad (Verstek, 2023)
This study aims to explain the legal considerations of judges in imposing criminal penalties on perpetrators of "eigenrichting" and to analyze the disparities contained in Decision Number 235/Pid.B/2017/PN.Brb and Decision Number 84/Pid.B/2017/PN .snt. This research is a normative legal research with a prescriptive nature of research and uses a case approach. This research shows that the basis of the judge's legal considerations in the two decisions both considered the elements in Article 170 paragraph (2) 3 of the Criminal Code, all of the defendants have been proven to fulfill the elements of the article. However, in legal considerations, the judge considers juridical aspects such as the indictment, elements of the articles charged, charges and pledoi, as well as non-juridical aspects such as the facts found in the trial. Apart from that, based on the judge's legal argument, what gave rise to the disparity in the two decisions was found in the judge's considerations, namely: 1. The aggravating and mitigating circumstances of the defendant; 2. The background of the defendant's actions; 3. As a result of the defendant's actions; and 4. Purpose of sentencing. Apart from that, other factors that cause disparity are the forgiveness of Decision Number 84/Pid.B/2017/PN.Snt and the provision of condolence money to the victim's family.Keywords : Disparity, Legal Considerations